Pandemic practice: Horror fans and morbidly curious individuals are more psychologically resilient during the COVID-19 pandemic. (1st January 2021) - Scrivner, Coltan; Johnson, John A.; Kjeldgaard-Christiansen, Jens; Clasen, Mathias
Abstract: One explanation for why people engage in frightening fictional experiences is that these experiences can act as simulations of actual experiences from which individuals can gather information and model possible worlds. Conducted during the COVID-19 pandemic, this study (n = 310) tested whether past and current engagement with thematically relevant media fictions, including horror and pandemic films, was associated with greater preparedness for and psychological resilience toward the pandemic. Since morbid curiosity has previously been associated with horror media use during the COVID-19 pandemic, we also tested whether trait morbid curiosity was associated with pandemic preparedness and psychological resilience during the COVID-19 pandemic. We found that fans of horror films exhibited greater resilience during the pandemic and that fans of "prepper" genres (alien-invasion, apocalyptic, and zombie films) exhibited both greater resilience and preparedness. We also found that trait morbid curiosity was associated with positive resilience and interest in pandemic films during the pandemic. Taken together, these results are consistent with the hypothesis that exposure to frightening fictions allow audiences to practice effective coping strategies that can be beneficial in real-world situations. Highlights: Fans of horror films exhibit less psychological distress during COVID-19. Fans of "prepper" films reported being more prepared for the pandemic. Morbidly curious people exhibit greater positive resilience during COVID-19. Morbidly curious people are more interested in pandemic films during the pandemic.